Simulation of Phobos gravity field estimation from Tianwen-1 flybys and implications for the modelling of Phobos' internal structure. Issue 1 (19th January 2023) - Guo, X; Yan, J G; Yang, X; Liu, L; Chen, Y H; Ye, M; Barriot, J P
ABSTRACT: Doppler radio tracking data from Tianwen-1, China's first Mars mission, could contribute to a better estimate of the gravity field of Phobos. In this study, we show that a determination up to degree and order 3 is feasible by considering five additional flybys of Phobos by the Tianwen-1 spacecraft, in addition to the previous flybys already done by the Mars Express spacecraft, and probably degree and order 5 is within reach. Three cases of mass repartition are considered: (i) a homogeneous case, (ii) a core-dominated Phobos, and (iii) a mantle-dominated Phobos. The case of a mantle-dominated Phobos is the easiest to detect, followed by a homogeneous Phobos, and finally by a core-dominated Phobos. We also discuss implications about the modelling of the internal structure of Phobos.